The Clavien-Dindo classification in pancreatic surgery: a clinical and economicvalidation - Téoule, Patrick; Bartel, Felix; Birgin, Emrullah; Rückert, Felix; Wilhelm, Torsten (Journal of investigative surgery, 2018)
Background/Aims: In 2004 P. A. Clavien and D. Dindo published the well-known grading system of postoperative complications. It is established in several surgical disciplines. The aim of this study was to assess its validity in pancreatic surgery. The impact of complication grade on economic resources was investigated as well. Methods: From a prospective database, we retrospectively evaluated all patients who underwent pancreatic resection between January 2009 and December 2014 at our department. 309 patients received pancreatic head resection (pylorus-preserving pancreatoduodenectomy (PPPD) or Kausch-Whipple), total pancreatectomy or left resection. We performed a univariate analysis of the correlation between the Clavien-Dindo classification-grade (CDC-grade) with length of postoperative stay (LOS) and DRG-related (diagnosis related groups) remuneration using Kruskal-Wallis test. Furthermore, we performed a subgroup analysis (chi-square test and Fishers-test) of demographic, clinical, and perioperative data. Results: American Society of Anesthesiologists (ASA) score (p = 0.0014), operation time (p = 0.0229) and intraoperative blood loss (p = 0.0016) showed significant correlation with CDC-grade. Increasing LOS and DRG-related remuneration correlated significantly with increasing CDC-grade (p < 0.0001). Conclusion: The CDC-grading system shows high correlation to clinical outcome and case-related remuneration in pancreatic surgery. Therefore, it is a valid tool for evaluation and comparison of surgical techniques and surgical centers.